Galaxy triplets in Sloan Digital Sky Survey Data Release 7-III: Analysis of Configuration and Dynamics - Duplancic Videla, Maria Fernanda (2014)
We analyse the spatial configuration and the dynamical properties of a sample of 92 galaxy triplets obtained from the Data Release 7 of Sloan Digital Sky Survey (SDSS-DR7; SDSS-triplets) restricted to have members with spectroscopic redshifts in the range 0.01 ≤ z ≤ 0.14 and absolute r-band luminosities brighter than Mr = −20.5. The configuration analysis was performed through Agekyan & Anosova map (AA-map). We estimated dynamical parameters, namely the radius of the system, the velocity dispersion, a dimensionless crossing-time and the virial mass. We compared our results with those obtained for a sample of triplets from the catalogue ‘Isolated Triplets of Galaxies’ (K-triplets) and a sample of Compact Groups. We have also studied a mock catalogue in order to compare real and projected configurations, and to estimate the three-dimensional dynamical parameters of the triple systems. We found that the SDSS-triplets prefer alignment configurations while K-triplets present a uniform distribution in the AA-map. From the dynamical analysis we conclude that the SDSS-triplets, K-triplets and Compact Groups present a similar behaviour comprising compact systems with low crossing-time values, with velocity dispersions and virial masses similar to those of low-mass loose groups. Moreover, we found that observed and simulated triplets present similar dynamical parameters. We also performed an analysis of the dark matter content of galaxy triplets finding that member galaxies of mock triplets belong to the same dark matter halo, showing a dynamical co-evolution of the system. These results suggest that the configuration and dynamics of triple systems favour galaxy interactions and mergers.